Testosterone : an unauthorized biography - Jordan-Young, Rebecca M., 1963-; Karkazis, Katrina Alicia, 1970- (Harvard University Press, 2019)
Testosterone is a familiar villain, a ready explanation for innumerable social ills, from the stock market crash and the overrepresentation of men in prisons to male dominance in business and politics. It's a lot to pin on a simple molecule. Yet your testosterone level doesn't in fact predict your competitive drive or tendency for violence, your appetite for risk or sex, or your strength or athletic prowess. It's neither the biological essence of manliness nor even "the male sex hormone." This unauthorized biography pries T, as it's known, loose from over a century of misconceptions that undermine science even as they make urban legends about this hormone seem scientific. T's story didn't spring from nature: it is a tale that began long before the hormone was even isolated, when nineteenth-century scientists went looking for the chemical essence of masculinity. And so this molecule's outmoded, authorized life story persisted, providing ready cause for countless behaviors--from the boorish and the belligerent to the exemplary and enviable. What we think we know about T has stood in the way of an accurate understanding of its surprising and diverse functions and effects. Rebecca Jordan-Young and Katrina Karkazis focus on what T does in six domains: reproduction, aggression, risk-taking, power, sports, and parenting. At once arresting and deeply informed, Testosterone allows us to see the real T for the first time.--